PENGARUH INSTAGRAM TERHADAP KEPUTUSAN BERKUNJUNG WISATAWAN DI TWA MANGROVE ANGKE - Yuniarta, Anisa; Putra, Gilang Pratama; Novarlia, Irena (STAH Dharma Sentana Sulawesi Tengah, 2024)
This study aims to analyze the effect of marketing through the Instagram platform on tourists' visiting decisions to Angke Kapuk Mangrove Nature Park in Jakarta. The background of this study is based on the decline in the number of visitors to Angke Mangrove Nature Park since the COVID-19 pandemic, despite intensified promotion through social media, especially Instagram. This research uses quantitative methods with descriptive data analysis techniques. Data collection techniques through questionnaires distributed to 100 tourist respondents who have visited Angke Mangrove Nature Park. The data that has been collected will be analyzed using the simple linear regression analysis method and using IBM SPSS Statistic 27 software. The results showed that marketing through Instagram has a significant influence on tourists' decisions to visit. This research is expected to increase the effectiveness of instagram development marketing on the Taman Wisata Alam Mangrove Angke account.